Preparation and physical and physical-chemical characterization of a brownie enriched with Moringa leaf flour (Moringa oleifera) (Research, Society and Development, 2020)
The moringa is an evergreen tree, which has gained notoriety because of some functional properties and for its diversification making it a good option for food use. The consumption and commercialization of cakes in Brazil has been growing, mainly with the trend of ready-to-eat foods. Based on these statements, it was carried out through the present work to prepare a chocolate brownie enriched with moringa flour (Moringa oliefera Lam.) And evaluate its physical and physical-chemical characteristics. The study was conducted at the Universidade Federal de Campina Grande campus Cuité. To obtain the flour, the moringa leaves were dried in an air circulation oven at 36ºC for 6h, crushed and sieved. From then on, three samples were prepared: BCP (without the addition of moringa flour); ECB (5% moringa flour) and BCM (10% moringa flour). The addition of moringa flour improved the physicochemical characteristics of the cake, where a higher ash content and less lipids were observed when compared to the standard sample. In addition, the addition of moringa flour increased the acidity of brownies. From the above, it appears that enriching the partial substitution of 5% and 10% of wheat flour with moringa flour does not present great differences between them. However, the use of moringa in food preparations is able to improve the physical-chemical composition of the final product.